STANDARISASI NON SPESIFIK EKSTRAK ETANOL DAUN KECAPI (Sandoricum koetjape Merr.) DAN EKSTRAK ETANOL DAUN KELUWIH (Artocarpus communis) - Maria Ulfah; Dhia Salsabilla; Evi Sukawati (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2019)
ABSTRACT The chemicals contained in an extract must be maintained its quality. The aim of this study is to prove both that the ethanol extract of kecapi (Sandoricum koetjape, Merr.) and keluwih (Artocarpus communis) leaves meet the non-specific parameters on the standardization of the extract. The ethanol extract of kecapi and keluwih leaves were extracted using the ultrasonic method. The extract was tested with non-specific parameters including water content, total ash content and metal contamination level. The test results are compared with standard parameter references. Ethanol extract of kecapi leaf have water content of 27.75% ± 1.708, total ash content of 4.856% ± 0.040 and levels of As metal contamination < 0.030 mg/Kg, Hg < 0.002 mg/Kg, Pb < 0.400 mg/Kg, while ethanol extract of keluwih leaf have water content of 23.206 ± 0.091%, total ash content of 9,678 ± 0.306% and levels of heavy metal contamination of As < 0.03 mg/Kg, Hg < 0.006 mg/Kg, Pb < 0.02 mg/Kg. The both extract meet the standard parameters of water content, total ash content and levels heavy metal contamination. Key words: kecapi leaves (Sandoricum koetjape, Merr.), keluwih leaves (Artocarpus communis), non-specific standardization